Patterns of care and survival for children with acute lymphoblastic leukaemia diagnosed between 1980 and 1994. Issue 3 (1st September 1999) - Stiller, C A; Eatock, E M
Abstract : AIMS: To document survival rates after acute lymphoblastic leukaemia (ALL) during the era of modern chemotherapy, to assess effects of prognostic factors at presentation, and to investigate the relation of survival to patterns of organisation of care. PATIENTS: From a population based series of 5078 children diagnosed in the UK during 1980–94, 4988 remained for analysis after exclusion of nine children ascertained from death certificates alone and 81 who received no antileukaemia treatment. MAIN OUTCOME MEASURES: Actuarial survival rates. RESULTS: Between 1980–84 and 1990–94, the proportion of children treated at paediatric oncology centres rose from 77% to 89%, and the proportion entered into national trials rose from 59% to 82%. Each of age, sex, white blood count, immunophenotype, and Down's syndrome status had a highly significant effect on survival. Five year survival improved from 67% in 1980–84 to 81% in 1990–94, a 42% reduction in the risk of death within five years of diagnosis. Survival did not differ significantly between hospitals with different numbers of new patients per year or between paediatric oncology centres and other hospitals. Children who were entered into national trials had higher survival and this difference became greater in recent years; five year survival rates for children diagnosed during 1980–84 were 70% and 64% for trial and non-trial patients, respectively; in 1990–94 the rates were 84% and 68% for trial and non-trial patients, respectively. CONCLUSIONS: Survival after ALL continues to improve. Nearly 50 children/year diagnosed during 1990–94 survived who would have died a decade before. Survival does not vary systematically with place of treatment but is higher for children entered into national trials.